2018
DOI: 10.1093/jxb/ery179
|View full text |Cite
|
Sign up to set email alerts
|

Powering the plasma membrane Ca2+-ROS self-amplifying loop

Abstract: This article comments on:Makavitskaya M, Svistunenko D, Navaselsky I, et al. 2018. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…These results reveal that Ca 2+ signaling is essential for melatonin-mediated CBF-responsive pathway and subsequent cold tolerance. [62,67]. Consistent with the previous findings, we found that H 2 O 2 and Ca 2+ interact, forming a reciprocal positive-regulatory loop that mediates melatonin-induced CBF pathway and cold tolerance (Figure 9).…”
Section: Ca 2+ Mediates Melatonin-induced Cbf-responsive Pathway and Cold Tolerancesupporting
confidence: 91%
See 1 more Smart Citation
“…These results reveal that Ca 2+ signaling is essential for melatonin-mediated CBF-responsive pathway and subsequent cold tolerance. [62,67]. Consistent with the previous findings, we found that H 2 O 2 and Ca 2+ interact, forming a reciprocal positive-regulatory loop that mediates melatonin-induced CBF pathway and cold tolerance (Figure 9).…”
Section: Ca 2+ Mediates Melatonin-induced Cbf-responsive Pathway and Cold Tolerancesupporting
confidence: 91%
“…As two crucial signal molecules, the interactions between H 2 O 2 and Ca 2+ signal have been well documented in various physiological actions, especially in defense against abiotic stressors [ 53 , 67 ]. For instance, stress-triggered Ca 2+ signal can phosphorylate and activate RBOHD via Ca 2+ -dependent protein kinase to generate H 2 O 2 , which in turn elicits a Ca 2+ signal through receptor-like kinases, such as GUARD CELL HYDROGEN PEROXIDE RESISTANT1, forming a self-propagating mutual activation loop between Ca 2+ and H 2 O 2 signals [ 62 , 67 ]. Consistent with the previous findings, we found that H 2 O 2 and Ca 2+ interact, forming a reciprocal positive-regulatory loop that mediates melatonin-induced CBF pathway and cold tolerance ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the ROS‐Ca 2+ self‐amplifying loop is gaining shape and has been shown to be involved in diverse plant responses (Pottosin & Zepeda‐Jazo, ). The knockout of AtGLRs like GLR3.1/3.5 or GLR3.3 leads to fewer transcripts of Ca 2+ sensing proteins and abolishes the stimuli‐induced changes in intracellular Ca 2+ concentration (Kong et al, ; Wudick et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The source depends on the relative expression of amine oxidases: mainly DAO in dicots and mainly PAO in monocots ( Moschou et al, 2008 ). Transmission of the external ROS signal to internal signaling is mediated by ROS-activated Ca 2+ influx, positively fed back to ROS production due to a Ca 2+ activation of the PM-bound NADPH-dehydrogenase ( Takeda et al, 2008 ; Demidchik et al, 2018 ; Pottosin and Zepeda-Jazo, 2018 ). In pea roots, OH • at lower and higher levels, respectively, induced a transient Ca 2+ pumping by Ca 2+ -ATPase and a sustained Ca 2+ influx via ROSIC ( Zepeda-Jazo et al, 2011 ).…”
Section: Effects Of Polyamine Catabolites: Ros and Gabamentioning
confidence: 99%